Diagnostic hallmarks and pitfalls in late-onset progressive transthyretin-related amyloid-neuropathy - Dohrn, Maike F.; Röcken, Christoph; De Bleecker, Jan L.; Martin, Jean-Jacques; Vorgerd, Matthias; Van den Bergh, Peter Y.; Ferbert, Andreas; Hinderhofer, Katrin; Schröder, J. Michael; Weis, Joachim; Schulz, Jörg B.; Claeys, Kristl G. (Journal of neurology, 2013)
Familial amyloid polyneuropathy (FAP) is a progressive systemic autosomal dominant disease caused by pathogenic mutations in the transthyretin (TTR) gene. We studied clinical, electrophysiological, histopathological, and genetic characteristics in 15 (13 late-onset and two early-onset) patients belonging to 14 families with polyneuropathy and mutations in TTR. In comparison, we analysed the features of nine unrelated patients with an idiopathic polyneuropathy, in whom TTR mutations have been excluded. Disease occurrence was familial in 36 % of the patients with TTR-associated polyneuropathy and the late-onset type was observed in 86 % (mean age at onset 65.5 years). Clinically, all late-onset TTR-mutant patients presented with distal weakness, pansensory loss, absence of deep tendon reflexes, and sensorimotor hand involvement. Afferent-ataxic gait was present in 92 % leading to wheelchair dependence in 60 % after a mean duration of 4.6 years. Autonomic involvement was observed in 60 %, and ankle edema in 92 %. The sensorimotor polyneuropathy was from an axonal type in 82 %, demyelinating or mixed type in 9 % each. Compared to the TTR-unmutated idiopathic polyneuropathy patients, we identified rapid progression, early ambulatory loss, and autonomic disturbances, associated with a severe polyneuropathy as red flags for TTR-FAP. In 18 % of the late-onset TTR-FAP patients, no amyloid was found in nerve biopsies. Further diagnostic pitfalls were unspecific electrophysiology, and coincident diabetes mellitus (23 %) or monoclonal gammopathy (7 %). We conclude that a rapid disease course, severely ataxic gait, hand involvement, and autonomic dysfunction are diagnostic hallmarks of late-onset TTR-FAP. Genetic analysis should be performed even when amyloid deposits are lacking or when polyneuropathy-causing comorbidities are concomitant.
Gesehen am 17.12.2020